THE DYNAMIC OF CLAIM BETWEEN ISRAEL AND UNITED STATES ON JERUSSALEM - Achmad Zulfikar; Muhammad Akbar Rahmadi; Irma wati (Dauliyah Journal of Islamic and International Affairs, 2019)
This study aims to analyze the dynamic of claim between Israel and United States on Jerussalem from the international law perspective. Al-Quds in Arabic means “The Holy One” which is another name of the city of Jerusalem. In its development Israel received strong support from the United States. This strong support was demonstrated by President Donald Trump in a statement on 6 December 2017 that Jerusalem (Al-Quds) is the capital of Israel. The statement gets the pros and cons of various parties in the world. This paper uses qualitative descriptive method and data collection through literature review. Finally, the study concludes that Israel and the United States based on consensus of UN member states can not make unilateral claims against Jerusalem (Al-Quds), because it is not in line with international law